Development of Blog-Based E-Learning Tools for Islamic Education Courses - Usri Usri (Edumaspul: Jurnal Pendidikan, 2022)
A research about developing e-learning tools was considered necessary to do towards the new normal era because the fact on the ground indicated that there were many teaching sources lacked of preparation when doing online learning. The kind of research that was implied was development research with ADDIE model which is Analysis, Design, Development, Implementation, and Evaluation. The subject was students of Tadris Bahasa Inggris major in Sekolah Tinggi Agama Islam Negeri Majene. The research development phases were firstly, analysis phase where it was found that the media used in online lecture were restrictedly Zoom application and Google Classroom with all their deficiency; Secondly, design phase done to follow up the issues found in the previous phase, that is by designing Learning Management System (LMS); Thirdly, development phase where the researcher made LMS based blog that completed with menus: RPS, RTM, Teaching Material, Discussion Forum, Quiz and Learning Program Evaluation; Fourthly, implementation phase done through trials of LMS four times of meeting; Lastly, evaluation phase where the evaluation results of the developed e-learning tools were considered already valid, very practical and effective